Effect of Pre-Growth Annealing on the Properties of Nonpurified Cadmium Telluride Single Crystals Obtained by Sublimation Method - Popovych, V.D.; Gnatenko, Yu.P.; Bukivskij, P.M.; Potera, P. (Ukrainian Journal of Physics, 2012)
The effect of high-temperature annealing of a nominally undoped CdTe charge under dynamic vacuum conditions on the electrical and optical properties of single crystals grown from this charge with the use of a modified physical vapor transport method has been examined. It is shown that the annealing results in the disappearance or an extinction of chlorine-related lines in the low-temperature photoluminescence spectra and the absorption bands in the long-wavelength absorption-edge spectra of the crystals concerned, as well as in a drastic fall of their resistivity. The observed alterations are explained by a removal of the Cl impurity during the annealing owing to a high volatility of chlorine compounds.